Misogyny in 'post-war' Afghanistan: the changing frames of sexual and gender-based violence. Issue 1 (2nd January 2018) - Ahmad, Lida; Anctil Avoine, Priscyll
Abstract: Although the US and NATO invasion of Afghanistan in 2001 was ideologically justified under the banner of democracy and women's rights, the latter issue has been completely forgotten within the public sphere since then. As the war has officially ended in Afghanistan, new forms of misogyny and sexual and gender-based violence (SGBV) have arisen. The 'post-war' Afghan context presents an institutional normalization of violence, favouring a culture of rape and impunity. The changing frames of violence against women are widely related to the political situation of the country: while public attention is focused on peace agreements, women's issues are relegated to banalities and depicted as 'everyday' news. Meanwhile, new frames of SGBV appear as body part mutilation within marriage, forced prostitution, and increasing domestic violence, partly due to the growing consumption of opium but also to the perpetuation of powerful warlords in state structures. This article draws on gender studies to analyse the current misogynist culture in 'post-war' Afghanistan, framing the new forms of violence induced by successive armed conflicts. It relies on interviews conducted in 2013 in Afghanistan; and on secondary sources, mostly taken from the Revolutionary Association of the Women of Afghanistan and Human Rights Watch reports.